2018
DOI: 10.1002/bio.3466
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive determination of bromhexine hydrochloride based on its quenching effect on luminol/H2O2 electrochemiluminescence system

Abstract: In this paper, the electrochemiluminescence (ECL) behavior of luminol/H O system in the presence of bromhexine hydrochloride (BrH) was investigated. It was found that the ECL intensity of luminol/H O system on a platinum electrode could be intensely quenched by BrH owing to the scavenging superoxide radical ability of BrH, and therefore the sensitive determination of BrH was possible. Under optimal conditions, the quenched ECL intensity was linear to the concentration of BrH in a wide range of 0.08 to 500 μM, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…According to review, bromhexine hydrochloride was determination by several methods such as these recent methods that employed reverse phase-high performance liquid chromatography (16,19) , spectrophotometry (14) , potentiometric-flow injection (11) , electrochemiluminescence system (12) , TLC densitometric (18) . Several techniques used for determination drugs and pharmaceuticals.…”
Section: Fig 1 Structure Of Bromhexine Hydrochloridementioning
confidence: 99%
“…According to review, bromhexine hydrochloride was determination by several methods such as these recent methods that employed reverse phase-high performance liquid chromatography (16,19) , spectrophotometry (14) , potentiometric-flow injection (11) , electrochemiluminescence system (12) , TLC densitometric (18) . Several techniques used for determination drugs and pharmaceuticals.…”
Section: Fig 1 Structure Of Bromhexine Hydrochloridementioning
confidence: 99%
“…Furthermore, BH-HCl is one of the mucous-modifying drugs that aid expectoration by improving the flow characteristics of bronchial mucous [3,4]. A literature review indicated the determination of bromhexine hydrochloride in dosage form, either in combined form or alone, by spectrophotometric [5][6][7][8][9][10][11], potentiometric [12], voltammetric [13], colorimetric [14], chemiluminescence [15,16], TLC [17], HPLC [18][19][20][21][22][23][24][25], RRLC-MS/MS [26], and HPTLC-HPLC [27]. This study presents a new method to determine BH-HCl in pharmaceutical formulations using tetraphenylborate as a precipitating reagent to form a yellowish-white precipitate with the use of a homemade instrument.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the accurate quantification of BHC in pharmaceutical products and clinical samples is critical [4]. Several analytical techniques have been employed for BHC analysis, including high-performance liquid chromatography (HPLC) [5], spectrophotometry [6], electrochemiluminescence [7], and potentiometric titration [8]. These methods require sophisticated and expensive instruments, which are often not available in low-resource areas.…”
Section: Introductionmentioning
confidence: 99%